Seeing is Believing: The Impacts of Visual Exemplars on American Young Adults' Reactions to Anti-Prescription Opioid Campaigns. (September 2021) - Cao, Xiaoxia; Xu, Jie
Many public health campaigns are designed to combat the opioid crisis in America. However, these campaigns are often ineffective or even counterproductive. To explore what contributes to the (in)effectiveness of these campaigns, an online experiment was conducted among a convenience sample of college students to test American young adults' reactions to four anti-prescription opioid campaign messages from local and national health organizations that vary in the presence of visual exemplars and statistical information. The study found that including a visual exemplar showing the negative consequences of misusing prescription opioids increased perceived susceptibility, psychological reactance, and perceived campaign effectiveness. The impacts of visual exemplars on psychological reactance and perceived campaign effectiveness were moderated by statistical information and (partially) explained by the believability of the campaigns.